Immigration's Role in Preventing and Resolving Human Trafficking - Kevin Aditya Putra; Maichel Fernando; Riri Wulandari (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Globalization has a variety of effects on the lives of individuals across the world, particularly in terms of meeting basic necessities and the economics of the community, ranging from the smallest to the largest. Globalization has resulted in a rise in the flow of people's traffic in each nation; Indonesia is one of the countries experiencing an increase in traffic flow at the moment. The impacts of increasing transportation movement around the world, including Indonesia, include cross-country or usually referred to as organized transnational crime, which poses a danger to every country on the planet. Organized transnational crimes come in a variety of forms, including people trafficking, people smuggling, narcotics trafficking, cybercrime, criminal acts of corruption, and terrorism. Which brings a great deal of attention to the globe, one of which is human trafficking, a crime that violates a person's rights as an autonomous human being with basic rights. In Indonesia, efforts to prevent and combat human trafficking are being made through improving the legislation and enforcement in the sector, as well as by fostering collaboration among government agencies and organizations involved in the fight. One of the agencies that have a direct relationship with human trafficking is immigration; because immigration has power over people's crossings, immigration plays a critical role in preventing and resolving human trafficking.